Bizarre Stromal Cells in an Endometrial Polyp. (June 2016) - Heller, Debra; Barrett, Theodore
Bizarre stromal cells have been reported in vulvovaginal polyps, as well as in nongynecologic sites, with caution not to mistake them for malignancy. Similar atypical stromal cells have only rarely been reported in the endometrium. We present a case found incidentally in a postmenopausal woman, and review the literature.